PRINSIP SOPAN SANTUN DALAM NOVEL DEMI ALLAH, AKU JADI TERORIS KARYA DAMIEN DEMATRA - Faleriana, Tia; Charlina, Charlina; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to analyze the principles of manners on the novel by God, I'm so Terrorist by Damien Dematra on the shape and scale of politeness contained in the novel. The method used is descriptive analysis method with qualitative approach. In this study, the authors used two techniques namely engineering documentation or literature and data collection techniques by reading a novel By God, I'm so Terrorist by Damien Dematra as a source of overall data, mark and underline every utterance in accordance with the forms of the principle of courtesy and scale politeness, identifying each utterance in accordance with the principles of courtesy and scale of politeness, classify the principle forms of courtesy and scale of politeness on the novel by God, I'm so Terrorist by Damien Dematra, and analyze and make a description of the principle of courtesy and scale of politeness on the novel by God , I'm So Terrorist by Damien Dematra. Data of this study totaled 95 data from the research I have found in this study is the shape and scale of politeness is the principle of courtesy shaped maxim of wisdom consists of twelve data, the principle of courtesy shaped maxim of generosity consists of fourteen of data, the principle of courtesy maxim shaped compliment consists of twenty data courtesy shaped simplicity principle consists of seven data, the principle of courtesy shaped match consisted of twenty-three of data, and the principle of courtesy shaped kesimpatian maxim consists of nineteen data.Key Words: principle of manners, forms the principle of courtesy, politeness scale